Factors influencing forces during laparoscopic pinching: Towards the design of virtual simulator. (June 2015) - Susmitha, Wils K.; Mathew, George; Devasahayam, Suresh R.; Perakath, Benjamin; Velusamy, Saravana Kumar
Abstract: Background: The design of good virtual simulators for laparoscopic training requires realistic visual and tactile perception. This is a study to characterize the factors that contribute to forces during laparoscopic pinching. Methods: Surgeons were divided into four groups according to years of experience in laparoscopic surgery. They were asked to grasp six different types of porcine abdominal tissue in a randomly sequenced manner, using two different types of sensorized graspers, under two regimes of perceptual feedback (with and without visual feedback). The forces (grasper handle force and grasper tip force) and grasper handle angle were recorded and analyzed. Results: The factors that determine forces during laparoscopic pinching can be ranked as follows: surgical experience (p < .001), tissue type (p = .007) and visual feedback (p = .033), but not grasper type (p = .071). Handle force depends significantly on surgical experience (p < .001), tissue type (p = .001) and visual feedback (p = .019), but not on grasper type (p = .203). Tip force depends significantly on surgical experience (p < .001) and marginally on tissue type (p = .082) and visual feedback (p = .053) but not on the grasper type (p = .180). Conclusion: Forces during laparoscopic pinching depend on surgical experience, tissue type and presence of visual feedback but not on grasper type. Our data can be an input in the design of virtual simulators with force feedback, for training laparoscopic pinching. Highlights: Determine factors that contribute to forces in laparoscopic pinching. Factors-surgical experience, tissue type and visual feedback; contribute to forces. Factor-grasper type did not contribute to the forces. The force information can be an input to the virtual simulators design.